Capture lengths of Prochilodus mariae in the upper of the Meta River, Colombian Orinoquia (Orinoquia, 2015)
Based on historical data of catch size and size at maturity of Prochilodus mariae obtained from 1980 to 2011, we aimed to establish if the average catch length per year and length at maturity of the population of the upper Meta River have experienced significant changes. Gathering data from fishing boats landing at Puerto Lopez, Meta, Colombia, we measured, weighed and sexed each caught specimen, obtaining 13444 records used to estimate average catches per year and per month, compared them annually, and performed correlation analyses between Metica River levels and ENSO anomalies. Length was estimated at 25%, 50% and 75% maturity for each year. Commercial catch length of P. mariae ranged from 14 to 45 cm SL, with differences in sex-specific length. The greatest average catch length for both females and males, 32,6 and 32 cm SL respectively, was observed in 1980, whereas in later years it varied in the range of 30 to 26,4 cm SL for females and 29 to 26 cm SL for males. The annual catch length cycle showed that the greatest average lengths occurred from April to June for females and May to June for males. Length at first maturity (L50) of females peaked at 33,5 cm SL in 1980, a significantly greater size than that observed in later years when it fluctuated between 27,1 and 31,8 cm SL. L50 of males remained within 25,8 and 29,5 cm SL throughout the period of study. Our findings show no overfishing impact on the growth and recruitment of P. mariae populations under fishing pressure within the area of study.Key words: River fisheries; length of gonadal maturity; migratory species; populations dynamics.
Keywords: River fisheries; length of gonadal maturity; migratory species; populations dynamics